BANKING SERVICES AND CUSTOMER PERCEPTION IN SOME SELECTED COMMERCIAL BANKS IN BANGLADESH: A COMPARATIVE PERSPECTIVE - Md. Mahi Uddin; Mohammad Aktaruzzaman Khan; Nadia Farhana (Indonesian Management and Accounting Research, 2014)
The banking system is facing challenges with stiff competition and advancement of technology. It becomes imperative for service providers to meet or exceed the target customers' satisfaction with quality of services expected by them. Hence, the present study attempted to study customers' perception of quality of services (both transactions-based and IT-enabled) in terms of its constituent factors and IT adoption in public, private, and foreign commercial banks in this E-age. The present investigation was planned with the objective to assess the extent of use of services especially the IT-enabled services in these banks and to analyze the constituent factors affecting customer satisfaction with the quality of services. The study area was Dhaka, the capital city of Bangladesh. Simple random sampling was used for selection of sample branches. The study reveals that check deposition and check clearance are the most popular banking services among the customers of all sample banks. The customers of nationalized banks were not satisfied with the employee behavior and infrastructure while respondents of private and foreign commercial banks were not satisfied with high charges, accessibility and communication. A small number of respondents were using IT-enabled services other than ATM, and a few respondents made complain against their respective banks. Keywords : Transaction-based banking services, IT-enabled banking services, Customer satisfaction, Service quality